Targeting interleukin-4 and interleukin-13 in the treatment of severe eosinophilic asthma - Nightingale Syabbalo (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2023)
Asthma is a chronic inflammatory airway disease affecting about 300 million people and responsible for 500,000 deaths annually globally. Eosinophilic asthma is one of the most common phenotypes of asthma. It constitutes about 50% to 60% of all cases of asthma, and it is the most common phenotype in children presenting with severe acute asthma. The mechanism of eosinophilic asthma is chronic airway inflammation which leads to airway hyperresponsiveness, and remodeling due to the immunopathological effects of inflammatory cytokines. The duet cytokines interleukin-4 (IL-4) and IL-13 play the most central role in the pathophysiology of eosinophilic asthma. The two sister cytokines are slightly similar with a 25% homology, they share a common signaling IL-4Rα chain, and have identical biological effects. Their principal biological effect is the development of Th2 cells from naïve T helper type 0 (Th0) lymphocytes. Th2 cells produce several cytokines responsible for inducing airway eosinophilic inflammation. They induce the ε isotype switch and the switching of the B cell immunoglobulin (Ig) production from IgM to IgE. Furthermore, they stimulate eosinophil proliferation, and migration to the allergic airways and promote eosinophil survival by suppressing eosinophil apoptosis. Activated eosinophils secrete several cytotoxic cationic proteins which damage the airway epithelium, and amplify the inflammatory cascade and airway remodeling. Most patients with eosinophilic asthma can achieve control on a long-acting β2-agonist, inhaled corticosteroid, and a leukotriene receptor antagonist. However, about 3.6-10% do not achieve asthma control. These patients usually benefit from treatment with a biologic. Dupilumab is the only biologic targeting IL-4 and IL-13 approved for the treatment of moderate-to-severe eosinophilic asthma. Clinical trials have shown that treatment with dupilumab results in good asthma control, and significantly reduces moderate-to-severe exacerbation rates (p < 0.001). Additionally, treatment with dupilumab has been shown to significantly improve lung function (p < 0.001), and health-related quality of life, and allows patients to taper or discontinue corticosteroid treatment.